The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4103/2229-5151.165007
|View full text |Cite
|
Sign up to set email alerts
|

Complications of pericardiocentesis: A clinical synopsis

Abstract: Pericardiocentesis (PC) is both a diagnostic and a potentially life-saving therapeutic procedure. Currently echocardiography-guided pericardiocentesis is considered the standard clinical practice in the treatment of large pericardial effusions and cardiac tamponade. Although considered relatively safe, this invasive procedure may be associated with certain risks and potentially serious complications. This review provides a summary of pericardiocentesis and a focused overview of the potential complications of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…When balancing the increased safety from combining echocardiographic and/or fluoroscopic guidance during percutaneous pericardiocentesis with the increased bleeding risk in thrombocytopenic patients with open surgical procedures, the clinical decision has gradually inclined toward the less-invasive approach without any apparent impact on long-term outcomes. Complication rates in this study were consistent with the low incidences reported in prior image-guided studies in non-thrombocytopenic patients, of anywhere between 4 and 20% (7,(20)(21)(22)(23). The decreased rate of complication we assume is due to using micropuncture technique and both echocardiographic and fluoroscopic guidance, and in comlex cases even triple-guidance with additional ultrasoundguided access.…”
Section: Discussionsupporting
confidence: 90%
“…When balancing the increased safety from combining echocardiographic and/or fluoroscopic guidance during percutaneous pericardiocentesis with the increased bleeding risk in thrombocytopenic patients with open surgical procedures, the clinical decision has gradually inclined toward the less-invasive approach without any apparent impact on long-term outcomes. Complication rates in this study were consistent with the low incidences reported in prior image-guided studies in non-thrombocytopenic patients, of anywhere between 4 and 20% (7,(20)(21)(22)(23). The decreased rate of complication we assume is due to using micropuncture technique and both echocardiographic and fluoroscopic guidance, and in comlex cases even triple-guidance with additional ultrasoundguided access.…”
Section: Discussionsupporting
confidence: 90%
“…Determination of signs or symptoms suspicious for cardiac tamponade is critical in the case of effusion findings on echocardiography. Urgent pericardial drainage is recommended in the case of tamponade [ 27 ]. The most common therapeutic option that was offered to patients in our study was pericardiocentesis (63.5%), followed by pericardial window (15.4%).…”
Section: Discussionmentioning
confidence: 99%
“…The true incidence of PDS is unknown: in a large retrospective analysis of 1,164 consecutive pericardiocentesis procedures, PDS was reported in only 1 patient, whereas in other series it has been reported in up to 4.8% ( 4 ). As is evident, this syndrome has no uniform clinical presentation and may be associated with both surgical pericardiostomy and pericardiocentesis, whereas the cause of pericardial effusions and clinical scenarios varies widely ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%